1980
DOI: 10.1079/bjn19800107
|View full text |Cite
|
Sign up to set email alerts
|

The early changes in retinol-binding protein and prealbumin concentrations in plasma of protein–energy malnourished children after treatment with retinol and an improved diet

Abstract: I . Changes in total retinol-binding protein (RBP), the holoprotein (holoRBP) and prealbumin (PA) concentrations have been monitored in plasma of thirty protein-and vitamin A-deficient preschool children from within a few hours up to 7 weeks after treatment with retinol and a good-quality protein diet.2. The children were classified into groups according to nutritional status as having either kwashiorkor, marasmus-kwashiorkor or marasmus, and given formula diets whose protein and energy contents increased step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…may increase rather than decrease RBP levels; however, previous studies showed that the RBP levels and molar ratio with both TTR and retinol are not affected by hypothyroidism (21). Vitamin A deficiency may also reduce the levels of RBP in the blood (23); however, in our patients, the levels of retinol were normal. Therefore, the reduced RBP levels in our patients indeed depend on malnutrition.…”
Section: Discussioncontrasting
confidence: 75%
“…may increase rather than decrease RBP levels; however, previous studies showed that the RBP levels and molar ratio with both TTR and retinol are not affected by hypothyroidism (21). Vitamin A deficiency may also reduce the levels of RBP in the blood (23); however, in our patients, the levels of retinol were normal. Therefore, the reduced RBP levels in our patients indeed depend on malnutrition.…”
Section: Discussioncontrasting
confidence: 75%
“…Since many years it has been demonstrated that alterations of retinol intake and vitamin A status affect hepatic release of RbP4 and circulating RBP4 [39][40][41]. A study in the vitamin A-deficient child reported that RbP4 accumulated in the liver during vitamin A deficiency which is released into plasma quickly after retinol uptake to form peak concentrations of total and holo-RbP approximately 3 h after dosing intramuscularly and 6 h orally [42]. Recently, RbP4 was found to be expressed and secreted by adipose tissue, however, RbP4 regulation by vitamin A in the adipose tissue has scarcely been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of RBP from the liver is strongly con trolled by the availability of vitamin A in the liver [24][25][26]. Thus, the lower RBP levels in group 2 patients reflect a diminished secretion of this protein from hepatocytes [27], Cycloheximide, puromycin and actinomycin are known to reduce general protein syn thesis [27].…”
Section: Discussionmentioning
confidence: 99%